Role of PCSK9 in the Development of Mouse Periodontitis Before and After Treatment: A Double-Edged Sword. (23rd December 2017) - Sun, Hua Ling; Wu, Yan Ru; Song, Fang Fang; Gan, Jing; Huang, Li Yuan; Zhang, Lu; Huang, Cui
Abstract : PCSK9 deficiency reduced Porphyromonas gingivalis (Pg)–induced inflammation-associated cytokine release in mice periodontal tissue. PCSK9 knockout alleviated Pg-induced mouse periodontitis by enhancing Pg and Pg-lipopolysaccharide clearance through CD36 and low-density lipoprotein receptor, but was detrimental to periodontal tissue regeneration after treatment. Abstract: Periodontitis is a highly prevalent infectious disease associated genetically with coronary heart disease (CHD). The effects of proprotein convertase subtilisin/kexin type 9 (PCSK9), a critical regulator of CHD, on periodontitis have not been studied to date. Here, we found that PCSK9 expression was increased in periodontitis patients and Porphyromonas gingivalis (Pg)–infected mice. Loss of PCSK9 attenuated Pg-induced periodontal bone loss in mice. First, PCSK9 deficiency reduced the release of inflammation-associated cytokines, such as tumor necrosis factor alpha (TNF-α) and interleukin 1β, in vitro and in vivo. Second, its deficiency enhanced Pg and endotoxin clearance during Pg invasion in part by upregulating CD36 and low-density lipoprotein receptor (LDLR), respectively. However, after berberine treatment, periodontal bone regeneration in the PCSK9 knockout group was significantly lower than that in wild-type. This was because PCSK9 overexpression promoted osteogenic differentiation of periodontal ligament stem cells (PDLCs) prechallenged by TNF-α. Furthermore, PCSK9 could rescue PDLC osteogenesis by repressing the NF-κB signaling pathway by interacting with TRAF2. These results suggest that PCSK9 may be a potent drug target for treating periodontitis.